Characterisation of extracts of Olibanum using supercritical fluid and hydro-distillation extraction methods - Babiker, Fatima; Jamal, Parveen (Universiti Teknologi Malaysia (UTM), 2017)
Frankincense, also known as olibanum, is the resin from the genus Boswellia. The substance has a long history of use in religious ceremonies and for perfume production. Its medicinal properties have now been appreciated for its healing properties. Supercritical Fluid Extraction (SFE) and Hydro-distillation Extraction (HDE) were used to obtain oil extracts from olibanum resin. The oil extracts were investigated for their antioxidant activity using 2,2- diphenyl-1-picrylhydrazyl (DPPH) inhibition assay and Fourier Transform Infra-Red (FTIR) and Gas Chromatography Mass Spectroscopy (GCMS) were used to characterise the oil extracts. SFE gave a higher yield compared to HDE, but HDE showed a higher antioxidant activity at every concentration tested. The result of GCMS and FTIR showed that the oil extracts contained some biological active compounds and bonds including terpenes and phenolics.